Competition between the thickness effects of each constituent layer in ferroelectric superlattices - Chew, Khian Hooi; Shin, F.G.; Ishibashi, Y. (2007)
We have used a lattice model based on the Landau-Ginzburg theory to examine the ferroelectric properties of a strongly coupled superlattice consisting of alternating ferroelectric and paraelectric layers. The thickness effects of the ferroelectric and paraelectric layers on the polarization behaviors of the superlattice are examined in relation to the dielectric softness of the paraelectric layer. Our finding suggests that the properties of the superlattice do not arise just from the intrinsic property of the ferroelectric layer alone, but depends on the behavior of the paraelectric layers. The competition between the thickness effects from the ferroelectric and paraelectric layers is found to play an important role in determining the properties of a superlattice.